2018
DOI: 10.1111/weng.12347
|View full text |Cite
|
Sign up to set email alerts
|

The English of Bosnia and Herzegovina

Abstract: With the number of world Englishes steadily increasing, the impact of ‘core’ English varieties is weakening. However, the influence of two varieties, namely standardised American English and standardised British English, seems to be dispersed across all areas, in particular across peripheral varieties. Due to the difference in their demographic weight and the institutional support they receive, these two varieties do not secure a balanced representation in the peripheral layer. The current study investigates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
(67 reference statements)
3
15
0
Order By: Relevance
“…There are mixed results in the literature concerning university students" preferences of English varieties in a multitude of contexts. British variant occupied a more prestigious position and it was the preferred variety by university-level students in countries such as Norway (Rindal, 2010) Spain (Carrie, 2017) and Finland (Koskela, 2017) while AmE was the more dominant variety among the participants in the context of Bosnia (Dubravac et al, 2018). More importantly, the research indicated that students" variety preferences affected their pronunciation models although their preferences did not necessarily correspond to their actual uses (Rindal, 2010).…”
Section: Literature Reviewmentioning
confidence: 90%
See 3 more Smart Citations
“…There are mixed results in the literature concerning university students" preferences of English varieties in a multitude of contexts. British variant occupied a more prestigious position and it was the preferred variety by university-level students in countries such as Norway (Rindal, 2010) Spain (Carrie, 2017) and Finland (Koskela, 2017) while AmE was the more dominant variety among the participants in the context of Bosnia (Dubravac et al, 2018). More importantly, the research indicated that students" variety preferences affected their pronunciation models although their preferences did not necessarily correspond to their actual uses (Rindal, 2010).…”
Section: Literature Reviewmentioning
confidence: 90%
“…However, it is important to note that these studies often explored one aspect of participants" English preferences, which was pronunciation. In a notable exception among the research in this particular strand was the study conducted by Dubravac et al (2018) in Bosnian context, where students favored AmE with respect to pronunciation and grammar while displaying no significant preference for a particular variety in terms of vocabulary and spelling. It is also noted in this study that the proliferation of the American variant in Bosnia seemed to affect learners" preferences in certain language areas despite of BrE being the traditional pedagogical model for these learners.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This gap between classroom English and everyday language suggests that the language of EFL classes tends to be more formal and uniform than any real spoken English. This happens out of necessity because there are so many different types of English, dependent upon such factors as cultural region, generation, and class, (Dubravac, Brdarević-Čeljo, & Bećirović, 2018). To be more practical , EFL materials and classes have to use a more standardised version of English.…”
Section: Competence and Credibility Of Native/non-native Efl Teachersmentioning
confidence: 99%